Assessing Pre-Service EFL Teachers’ Teaching Anxiety and Self-Efficacy during the Teaching Practicum: A Correlational Study - Diva Izzatul Islami; Nunung Suryati (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
The teaching practicum is a crucial phase for pre-service EFL teachers to shape their confidence and readiness to teach in the classroom. However, teaching anxiety often arises during this stage and may affect teachers’ self-efficacy. Although previous studies have examined these factors separately, limited research has explored their relationship in the Indonesian EFL context. This quantitative correlational study examines the relationship between teaching anxiety and self-confidence among 59 pre-service EFL teachers who had completed 4 months of teaching practice at schools, drawn from English Department students at a public university in Malang City, Indonesia. Data were collected using the adapted Foreign Language Teaching Anxiety Scale (FLTAS) and the Teachers’ Sense of Efficacy Scale (TSES), and analyzed using descriptive statistics and Pearson’s correlation in SPSS 27. The results show a pattern of teaching anxiety arising from several aspects and moderate beliefs about teachers’ self-efficacy. There is a significant weak negative correlation between teaching anxiety and self-efficacy (r = -0.287, p = .027), indicating that anxious teachers are less confident in their belief that they are competent in this area. This relationship shows that emotional challenges during teaching practice can hinder pre-service EFL teachers’ teaching confidence, underscoring the importance of teacher education programs in strengthening support during teaching practice and providing anxiety management strategies.